2007
DOI: 10.1007/978-3-540-77226-2_95
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neighbourhood Structure on Evolution of Cooperation in N-Player Iterated Prisoner’s Dilemma

Abstract: In multi-agent systems, complex and dynamic interactions often emerge among individual agents. The ability of each agent to learn adaptively is therefore important for them to survive in such changing environment. In this paper, we consider the effects of neighbourhood structure on the evolution of cooperative behaviour in the N-Player Iterated Prisoner's Dilemma (NIPD). We simulate the NIPD as a bidding game on a two dimensional grid-world, where each agent has to bid against its neighbours based on a chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In other versions of NIPD, players act on a lattice or arranged along a ring, and a player's behaviour depends on previous actions of the neighbours and if a neighbour has higher pay off, it may adopt its strategy (e.g. [21,38]). By contrast, in our model, interactions happen between two individuals, and in each interaction cost is paid only by the actor and benefit is received only by the receiver.…”
Section: Discussionmentioning
confidence: 99%
“…In other versions of NIPD, players act on a lattice or arranged along a ring, and a player's behaviour depends on previous actions of the neighbours and if a neighbour has higher pay off, it may adopt its strategy (e.g. [21,38]). By contrast, in our model, interactions happen between two individuals, and in each interaction cost is paid only by the actor and benefit is received only by the receiver.…”
Section: Discussionmentioning
confidence: 99%
“…A simple extension to the IPD, which we refer to as the N-IPD game (see [4,7,8,9,11,43]), is to modify the game so that multiple players play a version of the game at the same time. In the N-IPD, N players repeatedly interact with one another (where N > 2), making decisions independently based on two actions -cooperate or defect -without knowing the choices of other players.…”
Section: Iterated N-player Gamesmentioning
confidence: 99%
“…Numerous studies in the EGT literature have demonstrated that by restricting the interactions of players to local neighbourhoods/groups (Chiong, Dhakal, & Jankovic, 2007;Chiong & Kirley, 2009, 2011, 2012aKillingback & Doebeli, 1996;Nowak & May, 1992, 1993 or subdividing the population into groups (Killingback, Bieri, & Flatt,, 2006;Nunney, 1985;Traulsen & Nowak, 2006;Wilson 1990), cooperative behaviour can be promoted. Motivated by this, we hope to apply principles and findings from EGT to address issues in online study groups.…”
Section: Evolutionary Game Theorymentioning
confidence: 99%